Estudo comparativo de raízes de Jatropha mollissima sertão/praia, das castanhas de caju (anacardium occidentale l.) de diferentes plantios e estudo in vitro e in silico de compostos com potencial de inibição da enzima conversora de angiotensina. - Santos, Samuel José Mendes dos (2014)
Hypertension is a disease that affects millions of people around the world and among its main causative factors include an unhealthy diet, lack of physical exercise and obesity. Inhibition of angiotensin converting enzyme (ACE) has been identified as a therapeutic target for controlling high blood pressure because the octapeptide angiotensin II, which has vasoconstrictor activity, have minimized their activity in blood vessels. Compounds found in the bark of cashew nuts were separated and identified, and their potential for ACE inhibition was studied. It was observed that the anacardic acids possess this activity, being the 3-anacardic acid inhibitor best among the largest phenolic compounds extracted from the bark of cashews. In silico studies are currently performed to predict the bioavailability and the ability to penetrate the central nervous system (CNS) of a drug. We attempted to conduct this study to verify these properties in anacardic acids, as well as compare with other ACE inhibitors. It was observed that the anacardic acids infringe only one of the five rules of Lipinski, and as the rule states that at least three of these requirements must be satisfied, it is concluded that the anacardic acids exhibit good oral bioavailability and CNS penetration. Thus, the search for a cashew that provides a greater mass of LCC per extraction well as a greater amount of anacardic acid per kilogram of LCC becomes important. From this, it was found among five crops of dwarf cashew (CCP-76, CCP- 09, Embrapa-110, Embrapa-119 and Embrapa-109) which could offer a LCC with greater amount of anacardic acids. The cashew labeled CCP-76 gave a higher amount of LCC to about 30 grams per 50 grams of chestnut bark used for extraction and obtained a concentration of 185 grams per kilogram of anacardic acids LCC to be the best extraction of alkylphenols, among studied. In parallel to these studies, we sought to investigate differences existing compounds in Jatropha mollissima grown in different regions, and it was found that the stress of Ceará hinterlands increases the synthesis of substances for their survival. Thus, these plants can be used in preventive medicine, however, further study should be conducted.